Sustainable Use of the Sharing Economic Platform in Improving Quality of Service and Trust in Aceh, Indonesia - Nurma Sari; Wirdah Irawati; Fathurrahman Anwar; Ghrina Zikran; Syafira Amanda (AIBPM Publisher, 2022)
Economics is a crucial research topic because in the future the economy may be one way to support the economy. The objective of this study is to analyze the variables that affect the use of economic platforms that share primary data sources. The data was obtained through a questionnaire of 144 respondents, the data were then subjected to a multiple regression analysis. The findings revealed that one of the three exogenous variables, namely brand image did not affect creation, while service quality and trust had a strong and significant impact. Simultaneously shows significant outcome on the shared use of the platform economy. Quality makes the biggest contribution to influencing, so optimizing the implementation of quality and trust will help the development of the platform without harming users.